Interstitial lung disease with antibody–drug conjugates: a real-world pharmacovigilance study based on the FAERS database during the period 2014–2023 - Jing Shi; Xinya Liu; Li Wu; Yun Jiang; Yuanming Zhang; Yanfeng Wang (Therapeutic Advances in Respiratory Disease)
Background: Antibody–drug conjugates (ADCs) combine the targeted nature of monoclonal antibodies with the potent efficacy of small-molecule cytotoxic drugs. However, they also carry unique safety risks, including lung toxicity. Objective: To conduct a systematic review and analysis of ADC-related interstitial lung disease (ILD) incidence, characteristics, and risk factors to optimize safe and effective clinical use. Design: ADC-related ILD reports from the FDA Adverse Event Reporting System (FAERS) database between January 2014 and March 2023 were analyzed. Methods: ADC-related ILD reports were retrieved from the FAERS database. Statistical analyses were conducted using reporting odds ratio (ROR) and information components (ICs). The lower limit of the 95% confidence interval (CI) was set for ROR (ROR025) >1 or IC (IC025) >0, and statistical significance was determined based on a minimum of three reports. Results: The study analyzed the statistical data on ADC-induced ILDs (1277 cases). Trastuzumab deruxtecan was reported to be the most frequent (38.4%). Among the 33 preferred terms (PTs) in standardized MedDRA queries (SMQ) = “Interstitial lung disease,” the three most common were as follows: ILD (40.6%), pneumonitis (27.9%), and acute respiratory distress syndrome (ARDS) (7.6%). Trastuzumab deruxtecan showed the strongest association with ILD (PT) and pneumonitis, whereas ARDS was associated with four different drugs. The median time to onset of ADC-related ILDs was 51 days (interquartile range (IQR), 16–196), with ARDS having the earliest median time to onset at 15 days (IQR, 6–52). The onsets of pneumonitis, ILD, lung infiltration, and pulmonary toxicity were similar. More than 26% of ADC-related ILD cases result in death, with ARDS having the highest mortality rate of 65.0%. Conclusion: ADCs are associated with an increased risk of pulmonary adverse events, such as ILDs, with significant differences between drugs and varying mortality rates for different adverse events, necessitating distinct monitoring and appropriate management.